Social Media TikTok and Its Impact on Early Adolescents' Academic Concentration - Calista Agriffina; Ika Ariyati; Kushendar Kushendar (Suluh: Jurnal Bimbingan dan Konseling, 2026)
Background: The increasing use of social media among adolescents raises concerns about its impact on learning concentration. Students widely use TikTok because it offers engaging, easily accessible short videos. Aim: This study analyzes the relationship between TikTok use and learning concentration among early adolescents. Method: The study used a quantitative, correlational, cross-sectional design. The study population comprised N = 193 eighth-grade students at SMP Negeri 1 Kotagajah, with a sample of N = 138 selected via cluster sampling. Data collection was conducted using the Social Media Engagement Scale for Adolescents (SMES-A) with 11 items and a learning concentration scale with 28 items. Data analysis used product-moment correlation and simple linear regression. Results and Discussion: The results showed a correlation coefficient of -0.030 with a p-value of 0.725 (p > 0.05), indicating no significant relationship between the intensity of TikTok use and students' learning concentration. The regression results also showed that social media use accounted for only 0.1% of the variation in learning concentration. Conclusion: This finding indicates that social media use is not the main factor influencing students' learning concentration, as it is also influenced by other factors, such as learning motivation, interest in the subject, and the learning environment.